KLF4 Coordinates Corneal Epithelial Apical-Basal Polarity and Plane of Cell Division and Is Downregulated in Ocular Surface Squamous Neoplasia - Tiwari, Anil (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: Previously, we demonstrated that Krüppel-like factor 4 (KLF4) promotes corneal epithelial (CE) homeostasis by suppressing epithelial-mesenchymal transition (EMT) and TGF-β signaling. As TGF-β affects epithelial apicobasal polarity (ABP) and plane of division, we investigated the role of KLF4 in these processes. METHODS: Klf4 was ablated in adult ternary transgenic Klf4(Δ/ΔCE) (Klf4(LoxP/LoxP)/Krt12(rtTA/rtTA)/Tet-O-Cre) mouse CE using doxycycline chow. ABP and plane of division markers’ expression in Klf4(Δ/ΔCE) and human ocular surface squamous neoplasia (OSSN) tissues relative to controls was evaluated by quantitative PCR, immunoblots, and/or immunofluorescent staining. RESULTS: Klf4(Δ/ΔCE) CE cells displayed downregulation of apical Pals1 and Crumbs1, apicolateral Par3, and basolateral Scribble, as well as upregulation of Rho family GTPase Cdc42, suggesting disruption of ABP. Phalloidin staining revealed that the Klf4(Δ/ΔCE) CE actin cytoskeleton is disrupted. Klf4(Δ/ΔCE) cells favored vertical plane of division within 67.5° to 90° of the CE basement membrane (39% and 47% of the dividing cells relative to 23% and 26% in the control based on phospho-histone-H3 and survivin, respectively), resulting in more dividing cells within the Klf4(Δ/ΔCE) CE as reported previously. KLF4 was downregulated in human OSSN tissues that displayed EMT and downregulation of PAR3, PALS1, and SCRIB, consistent with a protective role for KLF4. CONCLUSIONS: By demonstrating that Klf4 ablation affects CE expression of ABP markers and Cdc42, cytoskeletal actin organization, and the plane of cell division and that KLF4 is downregulated in OSSN tissues that display EMT and lack ABP, these results elucidate the key integrative role of KLF4 in coordinating CE cell polarity and plane of division, loss of which results in OSSN.